PENGEMBANGAN E-MODUL BERBASIS PROBLEM-SOLVING PADA MATERI PEMANASAN GLOBAL - Medi Zahara (Indonesian Journal of Science Learning (IJSL), 2024)
Problem-solving based e-module developed in this research was based on the lack of teaching material in the science learning process and the difficulty of students in understanding Global Warming lesson at Telecommunication Junior High School Pekanbaru. This research aimed at developing teaching material that could be accessed through internet, knowing the validity level of e-module, knowing practicality test level by teacher, and knowing student response to the e-module. Research and Development (R&D) method was used in this research with development model by Borg and Gall with five research steps. E-module validity level was measured with assessments of content and problem-solving appropriateness was 85%, presentation appropriateness was 93%, linguistic appropriateness was 80%, and graphic appropriateness was 89%. With these results, e-module was stated very valid and appropriate to be tested. E-module practicality test was carried out by three science teachers was stated to be very practical, and it could be seen from the overall score 97% without revision and student response test was done by 18 students in the limited field test, the overall score was 85%, so it was stated very good. It could be concluded problem-solving based e-module on Global Warming lesson was valid and practical to be used as a teaching material.